Self-Oscillation-Based Frequency Tracking for the Drive and Detection of Resonance Magnetometers - Tian, Zheng (Sensors (Basel), 2016)
This paper reports a drive and detection method for Micro-Electro-Mechanical System (MEMS)-based Lorentz-force resonance magnetometers. Based on the proposed MEMS magnetometer, a drive and detection method was developed by using self-oscillation to adjust the mismatch between the mechanical resonance frequency and the coil drive frequency as affected by temperature fluctuations and vibration amplitude changes. Not only was the signal-to-noise ratio enhanced by the proposed method compared to the traditional method, but the test system automatically reached resonance frequency very rapidly when powered on. Moreover, the linearity and the measurement range were improved by the magnetic feedback generated by the coil. Test results indicated that the sensitivity of the proposed magnetometer is 59.6 mV/μT and its noise level is 0.25 μT. When operating in ±65 μT, its nonlinearity is 2.5‰—only one-tenth of the former prototype. Its power consumption is only about 250 mW and its size is only 28 mm × 28 mm × 10 mm, or about one-eighth of the original sensor; further, unlike the former device, it can distinguish both positive and negative magnetic fields. The proposed method can also be applied in other MEMS sensors such as gyroscopes and micromirrors to enhance their frequency tracking ability.